The Therapeutic Potential of Cannabinoids for Movement Disorders - Kluger, Benzi (Mov Disord, 2015)
BACKGROUND: There is growing interest in the therapeutic potential of marijuana (cannabis) and cannabinoid-based chemicals within the medical community and particularly for neurologic conditions. This interest is driven both by changes in the legal status of cannabis in many areas and increasing research into the roles of endocannabinoids within the central nervous system and their potential as symptomatic and/or neuroprotective therapies. We review basic science, preclinical and clinical studies on the therapeutic potential of cannabinoids specifically as it relates to movement disorders. RESULTS: The pharmacology of cannabis is complex with over 60 neuroactive chemicals identified to date. The endocannabinoid system modulates neurotransmission involved in motor function, particularly within the basal ganglia. Preclinical research in animal models of several movement disorders have shown variable evidence for symptomatic benefits but more consistently suggest potential neuroprotective effects in several animal models of Parkinson’s (PD) and Huntington’s disease (HD). Clinical observations and clinical trials of cannabinoid-based therapies suggests a possible benefit of cannabinoids for tics and probably no benefit for tremor in multiple sclerosis or dyskinesias or motor symptoms in PD. Data are insufficient to draw conclusions regarding HD, dystonia or ataxia and nonexistent for myoclonus or restless legs syndrome. CONCLUSIONS: Despite the widespread publicity about the medical benefits of cannabinoids, further preclinical and clinical research is needed to better characterize the pharmacological, physiological and therapeutic effects of this class of drugs in movement disorders.